An Appreciative Inquiry in a Mainstream Secondary School Into What is Perceived to Foster School Belonging for Pupils who Have Experienced School Suspension. - Gill, Victoria (2024)
School exclusion continues to be a common practice in England, with rates of suspensions rising every academic year. National data reports pupils in mainstream secondary schools as receiving the highest numbers of suspensions. Being suspended from school has been associated with negative outcomes such as feeling socially isolated from peers and staff. Conversely, school belonging has been defined as the feeling of being supported and accepted within school. Research suggests that a sense of belonging might serve as a protective factor against suspension, as it helps pupils to feel safe and valued within school. Using an Appreciative Inquiry methodology, this study aimed to explore what factors contribute to school belonging for pupils who have experienced suspension but remain at their mainstream secondary setting. Gaining the voices of this often-marginalised pupil population was integral to the study. Pupils and staff from a mainstream secondary school took part in this action research, providing their views which informed an action plan to be implemented in the school. Facilitating factors identified by participants included relationships which encouraged power-sharing, explicit encouragement from others, and support with learning following absence from lessons. Although an action plan was created, following an 8-week review, no actions had been completed due to changes within the school system. This suggests the complexity of secondary school systems and the potential barriers to implementing change to support inclusion for all pupils. Implications for practice are discussed, with consideration of local authorities and policy makers, and their involvement in creating environments which support all pupils to experience school belonging, as well as the role of Educational Psychologists, to continue to promote inclusion and the valuing of pupil voices.